تنفيذ إدارة وقف النقدي (دراسة حالة في وحدة المعاونة والجمع لأموال الزكاة والإنفاق والصدقة والوقف بيت المال هداية الله بماديون عام 2019- 2020 م) - Aqif Khilmia (University of Darussalam Gontor, 2020)
Waqf is one of the financial instruments that have an important position in Islamic civilization. Aside from being a source of funding for social, educational, and health activities, waqf can be used as alternatives for strengthening the community's economy. The potential of cash waqf in Indonesia every month is around 5.725 trillion rupiahs, assuming that all 229 million Indonesian Muslims donate 25 thousand rupiahs. To achieve optimal cash waqf management, it is necessary to have management in the cash waqf management agency so that the potential for cash waqf can be used optimally for the benefit of people. The purpose of this study is to determine the implementation of cash waqf management, in particular, the collection and distribution of cash waqf funds in the Assistance Unit for Baitul Maal Hidayatullah (UPP BMH) Madiun. This type of research is exploratory qualitative research. Data collection is done through observation, interviews, and study documentation. As for analysis, this study uses inductive analysis, deductive analysis, and content analysis to describe the research object. The results of the study explain that the implementation of cash waqf management in UPP BMH Madiun is managed by applying four management concepts which include Planning, Organizing, Actuating, and Controlling in collecting funds cash waqf. In the collection of waqf funds, Planning is in the form of periodic planning, namely annual, monthly, weekly, and housing and certain times. As for the aspect, it is Organizing carried out through the division of the Institution structure consisting of the chairman, HR and finance division, and fundraising. While actuating, it is carried out thoroughly in all divisions. The last aspect is Controlling which is directly under the supervision of the head of the institution assisted by the human resources and finance department. As for the distribution using the POAC method and adapted to what is needed by Madiun community, such as land acquisition, educational scholarship for a student of Tahfidz, construction of ablution places in various mosques as well as providing Al-Qur'an manuscripts.